Profissionais da mídia em São Paulo : um estudo sobre profissionalismo, diferença e gênero no jornalismo - Leite, Aline Tereza Borghi (2015)
The aim of this study is to analyze how professionalism, difference, gender and generation in the journalism career are articulated, from the exam of the journalists’ discourses in the city of São Paulo. We use up the concept of professionalism and the Sociology of the Professions theoretical reference, based on the contributions of Eliot Freidson and Julia Evetts to understand the values of journalism, the representations around what it would be the journalist’s function, the meaning of the changes in the profession, with the emergency of a new journalist’s profile, the relations of the profession with the learning at the universities and at the editorial rooms, the historical changes according to the orientation of the journal and the professional, and their specificities with reference to the process of professionalization of the journalism in Brazil. Our aim is to comprehend how female journalists are represented in different discourses of difference. For this, our approach is set on the Avtar Brah’s theoretical assumptions, highlighting the concept of difference as an analytical category and its several meanings. We have also based our analysis on other cultural studies agents that discuss about the decentralization of the subject and its identity, as the internal diversity that characterizes gender. Fifteen journalists were interviewed, women and men, who live and work in the city of São Paulo, of different generations who act in different types of media and with different types of hire in their relations of work. The selection of the interviewed women searched, contemplate single women professionals, married, with or without children, with different time of work, that represent the time dedicated to the personal and professional lives, corresponding to the impact of personal life in the construction of the career and to the possibilities to balance between these two dimensions in the social life.